Modeling of human center of pressure using a viscoelastic-supported inverted pendulum - Yoshikazu YAMANAKA; Katsutoshi YOSHIDA (Mechanical Engineering Journal)
Preventing falls is crucial for the elderly, and as an initial step, accurately quantifying their current balance abilities is essential. In this regard, the Center of Pressure (COP) has gained attention. This study proposes a novel mechanical model to accurately reproduce the human COP. If the proposed model can reproduce the human COP with high accuracy, it would enable the quantitative representation of human balance motion characteristics using model parameters. In this study, we first measured the time series of COP in a standing position from six subjects and constructed the Probability Density Function (PDF) of human COP. To reproduce this PDF, we propose a mechanical model that considers the human body as an inverted pendulum and the human foot as a triangular rigid body supported by viscoelastic material. The model control involves PD control incorporating randomness and dead-band effects. As a result, the proposed model successfully reproduced the characteristics, such as unimodal-peak and bimodal-peak patterns, observed in the human PDF by adjusting the control parameters. Specifically, the reproduction accuracy, which represents the agreement between the human and model PDFs, was over 87%, with an average of 96%. Moreover, we investigated the effect of model parameters on the PDF shape and clarified that increasing the effects of the PD control gain led to the emergence of unimodal-peak characteristics, whereas decreasing the gains resulted in bimodal-peak characteristics. Based on these results, we confirm that our proposed model can effectively parameterize human balancing behavior as observed in the PDF of COP.